Pathogenicity of Lecanicillium lecanii (Fungi) on the tick Boophilus microplus (Acari: Ixodidae) in the laboratory conditions - BELTRÁN-ALZATE, CATALINA; GUTIÉRREZ G., ANA ISABEL; SALDARRIAGA O., YAMILLÉ (Revista Colombiana de Entomología, 2008)
The pathogenicity of the fungus Lecanicillium lecanii on the cattle tick Boophilus microplus was determined under laboratory conditions. Ticks were submerged in solutions of three concentrations of L. lecanii (CIAT 215), 1,25 x 101, 1,25 x 105 y 1,25 x 108 conidia/mL, and these were placed individually in Petri dishes. Control ticks were submerged in distilled water. Statistical analyses showed significant differences in the period of preoviposition of females treated with L. lecanii between treatments and the control. In the period of oviposition there were significant differences between the controls and the concentrations 1.25 x 101, 1.25 x 105, and 1,25 x 108 conidia/mL. The survival of ticks showed differences between the control and the concentrations of L. lecanii. Of the 120 ticks inoculated, 115 (95,8%) were conidiated, and a total invasion was observed at ninth day. The percentage of emergence was notably reduced in all treatments compared with the control. A reduced survival of the larvae was observed at the concentration 1.25 x 108 conidia/mL (73%), compared with the control (100%). The concentration 1.25 x 108 conidia/mL of the fungus L. lecanii presented a significant effect on oviposition, the survival of the engorged females inoculated, the percentage of emergence of egg masses, and the survival of the larvae coming from the inoculated eggs of B. microplus.